Prevalence of distal surface caries in the second molar among referrals for assessment of third molars: a systematic review and meta-analysis. Issue 6 (July 2019) - Toedtling, V.; Devlin, H.; Tickle, M.; O'Malley, L.
Abstract: We conducted a systematic review of epidemiological studies to assess the prevalence of distal surface caries (DSC) in second molars adjacent to third molars. We searched the Cochrane Library, Lilacs, Embase, and Medline through Ovid ® (Wolters Kluwer) to retrieve English and non-English papers from inception to June 2016, and supplemented this with a search of the references and by tracking citations. Three reviewers contributed: one reviewed all the papers, and the other two divided the rest between them. They extracted data, completed structured quality assessments with a validated risk of bias tool for observational studies, and categorised the summary scores. The search yielded 81 records and 11 studies were analysed. The considerable methodological diversity meant that five were not eligible for inclusion in the quantitative synthesis. A meta-analysis of six studies on the prevalence of DSC and a subgroup analysis of three on various third-molar angulations were indicated. The overall pooled prevalence estimate calculated with a random-effects model was 23% (95% CI 2% to 44%) among patients. Prevalence subtotals were 20% (95% CI 5% to 36%) for prospective, and 15% (95% CI 5% to 36%) for retrospective studies among teeth. A subgroup analysis of three studies with 1296 patients (1666 molars) yielded a prevalence of DSC of 36% (95% CI 5% to 67%) for mesial impactions and 22% (95% CI 1% to 42%) for horizontal impactions. DSC was present in 3% of distally-inclined impactions, (95% CI 1% to 5%) and in 7% (95% CI 1% to 13%) of vertical third molars. The studies varied. The risk of bias was low in one and moderate in two. European studies suggested that DSC may be present in about one in four referrals for the assessment of third molars, and that the risk is considerably higher in those with convergent third molar impactions.